P256 Targeted stem cells expressing trail as a therapy for lung cancer tactical: a phase i/ii trial. (15th November 2017) - Davies, AV; Sage, EK; Kolluri, K; Weil, B; Rego, R Vitorino Tendeiro Pereira; Edwards, A; Bain, O; Santilli, G; Fullen, D; Champion, K; Day, A; Wheeler, G; et al.
Abstract : Introduction: Lung cancer is the leading cause of cancer death worldwide with over 70% presenting with incurable disease and few effective treatments. We previously demonstrated that mesenchymal stem cells (MSCs) transduced to express TNF-related apoptosis inducing ligand (TRAIL), will home to and induce apoptosis of tumour cells in vitro and reduce tumour growth in multiple in vivo models. We are now undertaking a clinical trial to assess the therapeutic efficacy of this genetically modified cell therapy. Aim: To evaluate the safety and anti-tumour activity of MSCTRAIL in combination with chemotherapy in patients with metastatic lung adenocarcinoma. Manufacturing Methods: MSCs were isolated from unrelated umbilical cord donors and characterised as MSCs according to international criteria. Cells from individual donors were thawed and transduced with a lentiviral vector encoding for TRAIL. Successful transduction was confirmed by flow cytometry and cells were subsequently pooled and seeded into a multilayer bioreactor. Once confluent, cells were harvested to form the primary seed stock (PSS). PSS vials underwent further expansion rounds to form a working cell stock (WCC) and subsequent investigational medicinal product (IMP) ready for patient dosing. Trial Design: Patients with stage IIIB/IV adenocarcinoma of the lung (EGFR and EML4-ALK negative) will be eligible for enrolment Phase I is a dose de-escalation study (figure 1A ) where patients will receive pemetrexed and cisplatin on day 1 then 4 × 10 8 MSC-TRAIL cells on day 2 of a 21 day cycle for 3 cycles. Dose limiting toxicities will be recorded. Phase II is a single blinded, randomised, placebo controlled trial consisting of standard chemotherapy and either MSC-TRAIL or placebo (figure 1B ). Safety data will be collected and efficacy will be assessed using CT with RECIST (v1.1) criteria at 12 weeks. All patients will be monitored for up to 2 years. Outcomes: Phase I primary outcome is safety and tolerability of MSC-TRAIL. Phase II is tumour response rate by RECIST (v 1.1) criteria at 12 weeks. Conclusion: We have produced a viable working bank of genetically modified stem cells, If therapy is effective we will plan to expand into larger phase III trials.